MOLECULAR IDENTIFICATION OF Charybdis affinis: A NEW RECORD OF SMOOTH-SHELLED SWIMMING CRAB FROM INDONESIAN WATERS - Zainuddin, Muhammad; Saputro, Suradi Wijaya; Sabdaningsih, Aninditia; Mudzakir, Abdul Kohar (Jurnal Segara, 2025)
This study aims to confirm the species identity of Charybdis affinis from the coastal waters of Tuban, Indonesia, using integrated morphological and molecular approaches. Specimens were examined based on morphological characteristics including carapace shape, anterolateral teeth arrangement, cheliped spination, and dorsal setation. Morphometric analysis showed carapace width ranging from 4.09–4.40 cm and length from 2.68–2.99 cm. Molecular identification was conducted using the mitochondrial cytochrome c oxidase subunit I (COI) gene. PCR amplification produced a 638 bp DNA fragment. BLAST analysis revealed 99.06% sequence identity with Charybdis affinis in GenBank with 100% query coverage, and the obtained sequence has been deposited in GenBank under accession number PV699569.1. Phylogenetic reconstruction using the Neighbor-Joining method showed that the samples clustered within the C. affinis clade and were clearly separated from closely related species. These findings confirm the first molecular record of C. affinis in Indonesian waters and demonstrate strong agreement between morphological and genetic characteristics. This study provides essential baseline information for biodiversity assessment and sustainable management of portunid crab resources.